Patient-Centered Care Transitions After Injury Hospitalization: A Comparative Effectiveness Trial. Issue 2 (1st May 2018) - Zatzick, Douglas; Russo, Joan; Thomas, Peter; Darnell, Doyanne; Teter, Harry; Ingraham, Leah; Whiteside, Lauren K.; Wang, Jin; Guiney, Roxanne; Parker, Lea; Sandgren, Kirsten; Hedrick, Margot Kelly; et al.
Abstract : Objective : The investigation aimed to compare two approaches to the delivery of care for hospitalized injury survivors, a patient-centered care transition intervention versus enhanced usual care. Method : This pragmatic comparative effectiveness trial randomized 171 acutely injured trauma survivors with three or more early postinjury concerns and high levels of emotional distress to intervention (I; n  = 85) and enhanced usual care control (C; n  = 86) conditions. The care transition intervention components included care management that elicited and targeted improvement in patients' postinjury concerns, 24/7 study team cell phone accessibility, and stepped-up care. Posttraumatic concerns, symptomatic distress, functional status, and statewide emergency department (ED) service utilization were assessed at baseline and over the course of the 12 months after injury. Regression analyses assessed intervention and control group outcome differences over time. Results : Over 80% patient follow-up was attained at each time point. Intervention patients demonstrated clinically and statistically significant reductions in the percentage of any severe postinjury concerns expressed when compared to controls longitudinally (Wald chi-square = 11.29, p  = 0.01) and at the six-month study time point (C = 74%, I = 53%; Fisher's exact test, p  = 0.02). Comparisons of ED utilization data yielded clinically significant cross-sectional differences (one or more three- to six-month ED visits; C = 30.2%, I = 16.5%, [relative risk (95% confidence interval] C versus I = 2.00 (1.09, 3.70), p  = 0.03) that did not achieve longitudinal statistical significance ( F (3, 507) = 2.24, p  = 0.08). The intervention did not significantly impact symptomatic or functional outcomes. Conclusions : Orchestrated investigative and policy efforts should continue to evaluate patient-centered care transition interventions to inform American College of Surgeons' clinical guidelines for U.S. trauma care systems.